Islamic Education Contribution on The Shifting of Madurese Women Social Relation - Halimatus Sa'diyah,; Sri Nurhayati,; Ali Muhammad al-Asma’i, (TADRIS: Jurnal Pendidikan Islam, 2024)
Starting with the significant rapid development of economic growth in Madura moreover the existence of cigarette Madurese workers, the authors are interested to study deeper about it and also the Islamic education contribution to the changing of Madurese social relations. Because of this phenomenon, shifting of social relations did not only happen in household relations but also massively happens in Madura. This research uses phenomenological approach to understand the phenomenon faced by the subject of the research, here the cigarette women workers. By using functional relation theory by Talcot Parson and social feminist theory by Fatimah Mernissi, the authors analyze this shifting and find the following results; social relation shifting pattern of madurese cigarette workers happens because of the increased understanding about gender relation, while the process of shifting can be seen In the patterns of family’s leaderships which are more democratic and responsive to women, and Madurese women have already been believed as leaders in some sides of society. Meanwhile, the Islamic education is the endogenous factor which grows and becomes the Madurese women’s characteristic so that Madurese women tend to firmly hold the Islamic norms in their lives. Madurese women’s social relation is built on the strong religious foundation and this makes the family and social life in Madura become the place to preserve worship.